Implementasi Program Penyuluhan Pertanian dan Dampaknya Terhadap Pemberdayaan Kelompok Tani di Desa Batu Belerang: Implementation of the Agricultural Extension Program and Its Impact on the Empowerment of Farmer Groups in Batu Belerang Village - Nursinar, Nursinar; Nurdin, Fadilah; Megawati, Megawati; Astaman, Putra (Jurnal Ilmiah Manajemen Agribisnis, 2025)
This study examines the implementation of an agricultural extension program in Batu Belerang Village and its impact on the empowerment of farmer groups. A quantitative survey of 83 respondents showed that program implementation was running well, characterized by the appropriateness of objectives, adequate resources, coordination, and commitment of implementers. Regression analysis demonstrated that program implementation (X2) had a positive and significant influence as the dominant factor on empowerment. Simultaneously, the independent variables had a significant influence with an Adjusted R² of 0.237, meaning that 23.7% of the variation in empowerment was explained by the model. The impact was seen in improved decision-making, member activity, and the implementation of innovations. In conclusion, the quality of program implementation is key to the success of empowerment. Therefore, improvements in planning, frequency of extension, and support for facilities and technology are needed for more optimal and sustainable results.